Benchmarking of Spin–Orbit Torque Switching Efficiency in Pt Alloys. Issue 8 (28th May 2020) - Hu, Chen‐Yu; Pai, Chi‐Feng
Abstract: A magnetic heterostructure with good thermal stability, large damping‐like spin–obit torque (DL‐SOT), and low power consumption is crucial to realize thermally stable, fast, and efficient magnetization manipulation in SOT devices. This work systematically investigates on Pt x Cu1‐ x /Co/MgO magnetic heterostructures with perpendicular magnetic anisotropy (PMA), and reports a promising spin Hall material, Pt–Cu alloy, possessing large DL‐SOT efficiency and moderate resistivity. The optimal Pt0.57 Cu0.43 has a large DL‐SOT efficiency of about 0.44, as determined by hysteresis loop shift measurements, with a relatively low resistivity (82.5 µΩ cm at 5 nm thickness). Moreover, this large DL‐SOT efficiency and the coercivity reduction accompanying with proper alloying contribute to a low critical switching current density (2.37 × 10 6 A cm −2 in the Pt0.57 Cu0.43 layer) in current‐induced magnetization switching measurements. Finally, the thermal stability of the Co layer can be preserved under alloying, whereas the switching power consumption can be significantly reduced, being the best performance among reported Pt‐based spin current sources. This systematic study on SOT switching properties suggests that Pt0.57 Cu0.43 is an attractive spin current source with moderate resistivity, large DL‐SOT efficiency, good thermal stability, and low power consumption for future SOT applications. Abstract : A magnetic heterostructure with good thermal stability, large damping‐like spin–obit torque (DL‐SOT) efficiency and low power consumption is the key to realize highly‐efficient spintronic memory devices. A new alloy system Pt–Cu is demonstrated to generate a greater DL‐SOT efficiency compared to pure Pt and other families of DL‐SOT sources, which is therefore ideal for low power consumption spintronic memory applications.